The Influence of Interest Rate, Exchange Rate, Profitability, and Liquidity on Stock Prices - Viska Fransisca; Etty Herijawati (Komunitas Dosen Indonesia, 2022)
This study intends to endlessly analyze the impact of interest rate, exchange rate, profitability on Gross Profit Margin, and Liquidity which are checked on the Current Ratio of Stock Prices. The object of this examination is the Food and Beverage Sub-Sector Manufacturing Companies recorded on the Indonesia Stock Exchange in 2017-2020. The technique in this examination is quantitative. Inspecting in this study utilizing purposive examining strategy and afterward chose upwards of 13 of 34 companies that match the predetermined standards. The information investigation method utilized is various straight relapse examination utilizing SPSS adaptation 25 program. The outcomes show that interest rates meaningfully not affect stock price, exchange rates not affect stock price, profitability which influences gross profit margin affects stock price, and liquidity connected with current proportion not affects stock price. All the while, Interest Rate, Exchange Rate, Profitability, and Liquidity influence the Stock Price.